Development of an equation for estimating appendicular skeletal muscle mass in Japanese older adults using bioelectrical impedance analysis. Issue 4 (23rd January 2014) - Yoshida, Daisuke; Shimada, Hiroyuki; Park, Hyuntae; Anan, Yuya; Ito, Tadashi; Harada, Atsushi; Suzuki, Takao
Abstract : Aim: Bioelectrical impedance analysis has been reported to have high reliability and accuracy in assessing body composition. However, equations for estimating appendicular skeletal muscle mass are population‐specific, and few have been developed for older Japanese adults. Thus, the purpose of the present study was to develop and validate an estimate equation for appendicular skeletal muscle mass using bioelectrical impedance analysis. Methods: A total of 250 older adults aged 65 years and older participated in this study. Appendicular skeletal muscle mass was measured using dual‐energy X‐ray absorptiometry, and bioelectrical resistance was measured using a multifrequency bioelectrical impedance analyzer. Multiple regression analysis was applied to derive sex‐specific estimation formulae using bioelectrical impedance analysis, and a Bland–Altman analysis was used to test agreement. Results: The cross‐validation results showed that the slopes and intercepts of the regression lines were approximately one and zero, respectively, and the coefficients of determination and standard errors of the estimate of the newly developed equations were similar between the two groups. Thus, the single sex‐specific equations were developed using all participants as follows. Men: appendicular skeletal muscle mass = 0.197 × (impedance index) + 0.179 × (weight) − 0.019 ( R 2  = 0.87, standard error of the estimate = 0.98 kg). Women: appendicular skeletal muscle mass = 0.221 × (impedance index) + 0.117 × (weight) + 0.881 ( R 2  = 0.89, standard error of the estimate = 0.81 kg). Conclusion: These new equations offer a valid option for assessing appendicular skeletal muscle mass in older Japanese adults.Geriatr Gerontol Int 2014; 14: 851–857.